2017
DOI: 10.17116/neiro201780770-73
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary spinal cord tumors and neurofibromatosis

Abstract: Our findings support a potential pathogenetic relationship between intramedullary tumors and neurofibromatosis. Astrocytoma was a predominant intramedullary tumor in patients with NF-1, while ependymoma predominated in patients with NF-2. IMSCTs combined with NF-1 occur predominantly in children and adolescents, while a combination with NF-2 is typical of young adults. Our findings confirm the fact that IMSCT surgery is required for a small number of NF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Conti et al stated that IMS associates with NF; however, several studies showed a prevalence of 0-2% in spinal tumours [7,70,80,103,125]. Our review found NF in 11 of 166 cases (6.6%).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Conti et al stated that IMS associates with NF; however, several studies showed a prevalence of 0-2% in spinal tumours [7,70,80,103,125]. Our review found NF in 11 of 166 cases (6.6%).…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, they commonly present as solitary lesions. To date, only five cases of multiple intramedullary schwannomas (IMS) have been described [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors correlate with ITs. The syndromes associated with these tumors are neurofibromatosis 1 (NF1, 19% of patients), 2 (NF2, 33-53% of patients), and Von Hippel Lindau disease (VHL) [4,5]. These patients develop mostly astrocytoma in case of NF1, ependymoma in NF2, and hemangioblastoma in VHL.…”
Section: • Metastatic Tumorsmentioning
confidence: 99%
“…Though rare, other histologies have been reported in NF1, such as gangliogliomas, primitive neuroectodermal tumors (PNETs), anaplastic astrocytomas, and even neurinomas have been reported anecdotally. [32][33][34] The surgical treatment for IMSCT consists in resection of as much tumor as possible guided by neurophysiological monitoring, to avoid further neurological deficits. Ependymomas and some pilocytic astrocytomas may be totally resected in some cases of focal and circumscribed tumors.…”
Section: Intramedullary Tumorsmentioning
confidence: 99%